The Problem of “Terms” in Translation from English into Arabic - al-Mawla, Fida Muhsin Matter (lark, 2019)
The word ‘term’ can be defined as “a word or expression that has a precise meaning in some uses or is peculiar to a particular field”, (A New Webster Dictionary, 1981:796). The point in a term is being a tool of gathering information, some qualities or features in the smallest linguistic semantic space, i.e., the utterance in which it replaces that particular notion, ( اسماعيل, 1987: 3). Kvam (2007:2) defines a “term” as ‘the systematic designation of defined concept within a specific field requiring specialized knowledge’. It is quite necessary for translators to be able to translate new terms from English into Arabic since the former is witnessing great invention and molding of new terms or neologisms. The problem of terms, as mentioned by Gentzler(1993: 16), has historically troubled translators. Besides, calling for one-to-one transfer approach and method revolves around decoding and recoding process increasingly difficult to hold. The present study is an attempt to shed some light on this aspect of translation. It is divided into two sections; the first of which is dedicated to new English terms or what is called neologisms and their translation into Arabic. Besides, it deals with formation of new terms semantically and morphologically. Section Two, on the other hand, focuses on some criteria for translating new terms and their application. The study ends up with some conclusions.